Discurso sobre o amor : o risco-zero na relação com a alteridade - Coutto, Isabel Osorio Tubino do (2008)
This doctoral thesis is about love discourses in modern times, when selfidentity melts into a personal project reflectively organized. Impelled to conduct his personal trajectory, the modern man seems to build an agenda for himself, with an obligatory feeling, that he has to be happy in all his existence segments. Love would be one more item, viewed as the main element, which has as its main goal to bring meaning and satisfaction to daily life. In this process, the future is continually thought over and man suffers when he has to decide on the risks he needs to eliminate. The media appear as a key element in this process, once they are the mediator between man and information, they are the one that possesses the knowledge, capable of creating reality. Through the means of communication, we observe two discursive paths which intend to classify love in two categories: biologic and culturally. But who is man who receives two distinct perspectives at the same time? To answer this question, we analyzed nine graders compositions, these essays are a reflexion of the behavior and love expectancies of a time marked by narcissism. The love discourses in modern times point at the existence of a fearful man who searches for selfpreservation at any cost, but who at the same time, wants to experience love. So, that s the great paradox of modern times: to love without taking any risks.